The institutional traps and externalities of the neo-industrial import substitution - K. A. Kolotov (Путеводитель предпринимателя)
Today in Russian economy the lack of investment resources for processing enterprises, the stagnation of the real and financial sectors interactions are observed. In such circumstances, the initiation of the import substitution process depends on the state’s participation in the process; however, it occurs in the institutional vacuum with the absence of mechanisms to coordinate the interests of government and business, entities of manufacturing and raw material producing industries in their technological recovery and domestic market saturation. This article describes the institutional traps, preventing the release of Russian economy on the path of neo-industrial development using the market, technological and social potential of import substitution.